Comportamento de geocélulas preenchidas com resíduo de construção e demolição como reforço de solo - Uhde, Bruna Thays (2020)
Civil construction is one of the sectors that most impacts the environment, both in the use of natural resources and in the production of waste. Infrastructure works need alternatives to reduce their environmental impact and to apply construction and demolition waste (RCD), considered a material with great potential for reuse. Reinforcement using geocells has already been studied by other researchers and is showing efficiency. Made of geosynthetic materials, its cells provide confinement to the ground, which improves the distribution of shipments. Thus, the study proposes an alternative to natural aggregates replacing them with RCD, and analyzing their behavior as filling material for geocells used in the reinforcement of sandy soil, in order to analyze the performance of the residue in increasing the load capacity of the soil. The verification of the resistance results of the samples was obtained through laboratory plate tests on a circular plate of 15 cm in diameter, with direct measurements of tension and displacement. The tests were carried out in duplicate for two different geocell heights filled with RCD, in order to further analyze this influence on soil resistance. As well as samples of residue without geocell were tested at the same heights, to verify the real increase in the load capacity of the soil provided by the use of the geocell. The results showed that the RCD as filling material and the geocell promoted an increase of 2.57 times for the 20 cm tests and 2.38 times for the 7.5 cm tests compared to the reference. As well as the results for the reduction of displacement of the shoe presented more than 70% improvement when compared with the reference and more than 40% when compared with the residue, with no influence of the height of the reinforcement for the geocell tests.